About the "word-theme" (Signifiances (Signifying), 2019)
Reflection on theoretical, methodological and critical issues involved in Saussure’s questioning of the –“symbolic” and “diabolic”– link between signifier and signified when giving a conceivability of sound-thought by assuming the existence of what he identifies as a “theme-word” (Stichwort).